2017
DOI: 10.1186/s13229-017-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy in mouse models of Rett syndrome is related to the severity of Mecp2 mutation and behavioral phenotypes

Abstract: BackgroundRett syndrome (RTT) is a neurodevelopmental disorder that predominantly affects girls. The majority of RTT cases are caused by de novo mutations in methyl-CpG-binding protein 2 (MECP2), and several mouse models have been created to further understand the disorder. In the current literature, many studies have focused their analyses on the behavioral abnormalities and cellular and molecular impairments that arise from Mecp2 mutations. However, limited efforts have been placed on understanding how Mecp2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Previous studies reported decreased volumes in the cerebrum (Reiss et al, 1993;Casanova et al, 1991;Murakami et al, 1992;Subramaniam et al, 1997;Carter et al, 2008), basal ganglia (Reiss et al, 1993;Casanova et al, 1991;Murakami et al, 1992), cerebellum (Casanova et al, 1991;Murakami et al, 1992), corpus callosum (Murakami et al, 1992), and brainstem (Reiss et al, 1993;Murakami et al, 1992) in RTT compared to those in NC. The volume reduction of the cerebrum and the cerebellum have been confirmed in brain MRI studies with a mecp2 hetero-or homozygousknockout mouse model (Ward et al, 2008;Allemang-Grand et al, 2017;Saywell et al, 2006). However, in our study, a statistically significant difference between RTT/RTT-l and NC was observed only in the cerebellar volume.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies reported decreased volumes in the cerebrum (Reiss et al, 1993;Casanova et al, 1991;Murakami et al, 1992;Subramaniam et al, 1997;Carter et al, 2008), basal ganglia (Reiss et al, 1993;Casanova et al, 1991;Murakami et al, 1992), cerebellum (Casanova et al, 1991;Murakami et al, 1992), corpus callosum (Murakami et al, 1992), and brainstem (Reiss et al, 1993;Murakami et al, 1992) in RTT compared to those in NC. The volume reduction of the cerebrum and the cerebellum have been confirmed in brain MRI studies with a mecp2 hetero-or homozygousknockout mouse model (Ward et al, 2008;Allemang-Grand et al, 2017;Saywell et al, 2006). However, in our study, a statistically significant difference between RTT/RTT-l and NC was observed only in the cerebellar volume.…”
Section: Discussionsupporting
confidence: 77%
“…Although Pcdhg GcKO mice are smaller, brain size can vary independently from body size (Allemang-Grand et al, 2017;Ellegood et al, 2013). To identify structure-specific differences, the brains were segmented into 182 regions and measured as percent volume differences from control.…”
Section: Gabaergic Pcdhg Mutants Display Reductions In Brain Volume Amentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) studies in Rett syndrome patients also found a significant reduction in fractional anisotropy (FA) in the corpus callosum (Mahmood et al 2010). MRI studies have also shown alterations in cerebellar white matter, and corpus callosum of all available MeCP2 mutant mice currently available (Allemang-Grand et al 2017). These results correlate with white matter impairment seen in human Rett syndrome patients.…”
Section: Oligodendrocytes and Mecp2mentioning
confidence: 88%